Molecular guardians: Unveiling chitosan film defense through analytical microscopy - Rohi, T; Chitra, R; Thamarai Selvi, S P; Alagu, M P; Maragatham, S S (Plant Science Today, 2025)
In response to growing environmental concerns about plastic packaging, this study examines biopolymer-based alternatives, focusing on the development and performance of chitosan-based films enhanced with polyvinyl alcohol (PVA), polyethene glycol (PEG), glycerol and essential oils as eco-friendly packaging solutions. Using the solvent casting method, chitosan films were prepared with incorporated essential oils to enhance their functional characteristics. FTIR analysis confirmed the successful fabrication of the films by identifying functional groups such as -OH, N-H, C=O, C≡N, C-Cl, C-Br and metal-O bonds. SEM analysis revealed smooth surfaces with minimal residues, indicating partial uniformity. Antimicrobial testing revealed that sample S1 exhibited concentration-dependent inhibition, whereas sample S2 demonstrated strong, broad-spectrum activity against Staphylococcus aureus and Escherichia coli at higher concentrations. Antioxidant activity, evaluated using the DPPH assay, revealed that at 10 µL of sample S2, 76.22 % inhibition was achieved and sample S1 showed 75.40 %, with effectiveness declining at higher concentrations. The findings underscore the promise of chitosan-essential oil films as multifunctional packaging materials with both antibacterial and antioxidant properties. In horticultural applications, these biofilms present a sustainable alternative to traditional plastics, contributing to improved product quality and extended shelf life during postharvest processes and marketing.